Modal Sosial Masyarakat di Kawasan Penyangga Taman Nasional Gunung Ciremai untuk Mendukung Skema Pengelolaan Berbasis Kemitraan - Rahmat Hidayat; Djoko Marsono; Sahid Susanto; Ronggo Sadono (Jurnal Wilayah dan Lingkungan, 2020)
Understanding about social capacital of community has an essential role in supporting the collaborative management of conservation area. This study aims to assess the characteristics of elements of social capital and measure the relationship of the effects of elements of social capital on social capital owned by communities around the buffer zone of Taman Nasional Gunung Ciremai (TNGC). Study site was located in the upstream area of Cisanggarung watershed. Data collection was undertaken through three stages, i.e. literature study, field observation, and inteview. The analysis was conducted using confirmatory factor analysis and descriptive test. The results demonstrated that the social capacital of communities around the buffer zone of TNGC, even though in the same watershed ecosystem unit they had varied characteristics. This fact is proven by the differences in social capital categories and the most influential elements of social capital in the formation of social capital in rural areas that are buffer zones. In order to support the collaborative management in TNGC, the sub-elements of social capital which is at a very weak and weak level, as well as the most influential social capital element in the formation of social capital in each village, should be the main consideration in increasing social capital and preparing conservation collaborative programs that are will be done in each village.